Leveraging ICT Platforms to Foster Citizen Engagement For Enhanced Public Accountability : The Korean Experience - Bae, You-Jin; Choi, Seung Won; Kim, Min Jeong; Kim, Seongjun (World Bank, Washington, DC, 2019)
This learning note aims to document the experience of the Board of Audit and Inspection of Korea (BAI) and the online administrative appeals hub system of Korea’s Central Administrative Appeals Commission (CAAC) in leveraging ICT platforms for citizen engagement. The note both analyzes participatory practices and examines how the use of ICT platforms contributed to enhance public outreach by making citizen engagement in public accountability more cost-effective, scalable, transparent, and inclusive. The learning note targets accountability institutions (such as supreme audit institutions, anti corruption agencies,and so on), as well as representatives from civil society organizations and citizens around the world interested in knowing more about the experience of Korea, including the challenges and opportunities, in leveraging ICT tools to foster citizen engagement for enhanced public accountability.